Electrochemical Performance Of Sacrificial Anode Metals In Preventing Corrosion On Ships: A Literature Review - Anwar, Syairi; Octavitri, Yollanda; Purnaningratri, Indah; Sofian , Ian Mochamad (Pelopor Publikasi Akademika, 2025)
Corrosion is a major issue for ships operating in high-salinity seawater environments. One of the most widely applied methods of corrosion prevention is cathodic protection using sacrificial anodes. This article presents a literature review on the effectiveness of various metals used as sacrificial anodes, including zinc (Zn), aluminum (Al), and magnesium (Mg). The review highlights that each metal has unique characteristics: zinc offers stable potential and moderate service life, aluminum provides high current capacity with lightweight properties, while magnesium delivers the highest protective potential but corrodes rapidly in seawater. The selection of sacrificial anode material depends on ship operating conditions, water resistivity, and economic considerations. This review serves as a reference for the maritime industry in designing effective and cost-efficient cathodic protection systems.